A PHY/MAC Cross-Layer Analysis for IEEE 802.15.7 Uplink Visible Local Area Network - Ngoc T. Dang; Vuong V. Mai (IEEE Photonics Journal)
Supported by IEEE 802.15.7 standardization activities, visible local area network (VLAN) has been gaining popularity in recent years. Specified in the standard are physical (PHY) and uplink medium access control (MAC) layers of VLAN. However, there is a lack of studies on the MAC performance analysis and improvement under the effects of PHY transmission errors in the literature. We thoroughly analyze the MAC for various performance metrics taking into account PHY transmission errors due to different VLC physical factors. We also consider MAC enabling frame retransmissions as a solution to PHY transmission errors. Numerical results show that, first, MAC performance is critically affected by PHY transmission errors and, second, frame retransmissions, with a proper setup, could considerably improve the performance.